Failure notification mechanism based on serial communication and same source and its application in ASON - WANG Xian-xi; WANG Miao; LU Yue-ming; JI Yue-feng (Tongxin xuebao)
By extending the functions of RSVP-TE, a new mechanism of failure notification based on serial communication and same source was proposed. Since serial communication mechanism was introduced, it could achieve failure notification according to source of connections affected by failure, and made contribution to failure recovery rate and failure recovery time. Experiments were implemented in a 15-node-ASON test-bed. And the results show that, compared with traditional failure notification mechanism, the new mechanism can avoid the conflicts of resource reservation in the process of network failure recovery to a certain degree. With this new mechanism, network failure recovery rate is effectively increased by 21% and network failure recovery time is shortened by 15% in the testing network with 5 000 connections.